Actual competence, rather than perceived competence, is a better predictor of physical activity in children aged 6-9 years. Issue 13 (3rd July 2018) - McIntyre, Fleur; Parker, Helen; Chivers, Paola; Hands, Beth
ABSTRACT: There is a limited understanding about the relative importance of perceived and actual competence on emergent physical activity levels in children and whether there is a difference in their development and strength between boys and girls. This study used a single-cohort, multiple age group design to monitor physical activity, actual motor competence (AMC) and perceived competence (PC) on four occasions over 18 months in 6-to 9-year-old boys and girls (N = 201). Physical activity was measured by 7-day daily step counts (pedometer) and activity diary. AMC was assessed by mastery of skill criteria for 4 motor skills; run, overhand throw, standing broad jump, and line walk. PC was measured with the Self Description Questionnaire-I. Linear Mixed Model analysis revealed that AMC, Gender and School significantly impacted physical activity levels longitudinally in these children. AMC made a greater contribution (9-30%) to physical activity levels than PC (0-5%), and at an earlier age in boys (7 years) than girls (9 years). The need to acknowledge these developing distinctions in considering emergent physical activity levels has important implications for childhood learning environments and physical activity interventions.